El sentido de vida en cuidadores familiares de personas en situación de enfermedad crónica: una mirada desde Viktor Frankl (2015)
The following essay has to do with the theoretical approaches related to the topic, "The Meaning Of Life For Family Caregivers Of People Who Are Affected By Chronic Disease, From The Perspective Of Viktor Frankl", demonstrating through an argumentative and purposeful approach ways that the meaning of life can have for those that due to their proximity to the person going through a situation of chronic disease is to become their family caregiver. Theoretical approaches have been developed from the perspective of the author Viktor Frankl, in terms of the meaning of life. At the same time we defined several terms that were considered for an overview of the subject. After this exercise there was an articulation and integration of the concepts developed reviewing topics such as: palliative care; chronic disease; family caregivers and the meaning of life; in the experience of being primary caregiver of a person in a situation of chronic disease. Estudios clínicos y sociales.-- Línea de Investigación: transformaciones contemporáneas y psicología humanista existencial.-- Área: psicología. Semillero KIRON.-- Tema: cuidados paliativos.